Product Quality and Brand Trust Analysis on Customer Loyalty at Zetqlo Apparel in Bandung City - Priadi, Agam Fazri; Lestari, Fitri (Banking & Management Review, 2024)
Introduction/Main Objectives: The purpose of this study is to determine how customer loyalty at Zetqlo Apparel in Bandung is affected by product quality and brand trust. Zetqlo, a jersey brand founded in 2018, has faced fluctuating sales from 2021 to 2023 due to concerns over declining product quality, which has eroded customer trust. Background Problems: The study investigates the problem of how declining product quality has affected customer loyalty, addressing the research question: How do product quality and brand trust influence customer loyalty at Zetqlo? Novelty: While existing research has explored product quality and brand trust individually, this paper focusses on their combined effect on customer loyalty within a local fashion brand context, an area that has been underexplored in Bandung. Research Methods: The study employs a quantitative approach, with data gathered from 100 respondents using purposive sampling. A structured questionnaire based on a Likert scale was used, and multiple regression analysis was applied to evaluate the relationships between the variables. Findings/Results: The analysis shows that product quality significantly and positively affects customer loyalty, while brand trust has no significant direct impact. However, product quality and brand trust together account for 73.9% of the variance in customer loyalty. Conclusion: The study concludes that maintaining high product quality is essential for sustaining customer loyalty at Zetqlo, while improvements in brand trust are also necessary. These findings suggest that enhancing both product quality and communication efforts is key to Zetqlo’s continued success in a competitive market.